The effects of tourism, economic development and population growth on a small rural area of South Africa. Issue 2 (4th May 2019) - Bate, G. C.; Taylor, R. H.
Abstract : The Maputaland coastal plain is situated on the north-east coast of South Africa. It is important to the South African economy because of the number of game parks that draw tourists to the area and South Africa. Essentially a rural area with a relatively small local population, the introduction of forestry plantations in the 1950s resulted in opportunities for the local Maputaland people. The war in Mozambique in the latter 20th century resulted in many South Africans not holidaying in that country. This prompted the then Natal Parks Board to establish beach and sea-based holiday facilities at Sodwana early in the 1970s. This is an area that is now within the iSimangaliso Wetland Park World Heritage Site. The establishment of forestry resulted in an inflow of people to the area eager to obtain employment. A steady rise in the number of tourists to the area further improved the availability of jobs. There has been a rise in the annual numbers of visitors utilising the facilities of the area. The provision of water includes a municipal supply from Lake Sibaya that is treated in the town of Mbazwana and piped to local residents. This service has become inadequate causing dissatisfaction. Added to the problem has been the development of a considerable number of private holiday establishments additional to the Sodwana facility situated outside the Park and therefore outside its jurisdiction. The increased number of people living in and visiting the area has meant that the original local municipal water supply became totally inadequate, resulting in the sinking of boreholes by both local people and the commercial holiday facility operators. There is no municipal sewage system in the area and waste water is discharged into the ground and hence into the groundwater. This has resulted in borehole water showing higher than natural levels of nutrients that in turn are having an adverse impact on the quality of the groundwater, the lakes and the estuary in the area. To protect the local ecosystem and economy it is important that a formal sewage system be provided. Disposal of household waste from the area will be difficult because of the terrain and will have to be carefully planned to provide an adequate system that will protect the natural environment which attracts tourists and is the basis of the local economy.